Pinus gerardiana Wallichex. D. Don. -A review - Gajender Singh; Deepak Kumar; Ashutosh K. Dash (Elsevier, 2021)
Background: Pinus gerardiana Wallich ex. D. Don. (Chilgoza) is a popular medicinal plant that is used in several traditional medicines to cure various diseases. It is reputed as the "Champion of Rocky Mountains" in the interior Himalayas of India. Besides India, its habitat prevails in the Tibet area of Baluchistan (Pakistan), Afghanistan, etc. The plant is jeopardized in Red Data Book of India. For its survival, there is a prerequisite of adequate knowledge on the plant's involvement towards human health and other activities. Purpose: The objective of this review article is to share sufficient literature evidence regarding the plant Pinus gerardiana Wallich ex. D. Don. a frequently used Ayurvedic medicine in Asian countries abide by Himalayan belt. Beside this other information regarding molecular study, nutraceutical values, disadvantages too has been mentioned. Method: This article reviews detailed information of Pinus gerardiana Wallich ex. D. Don. Pharmacgnosy, Chemical information rlated to the isolated molecules from different extracts, pharmacological applications, Ethnomedicinal applications such as health benefits of plant, nutraceutical value of the seed, were reported till date. Articles for the citations were acquired all the way through a methodical search using electronic publications such as PubMed, Scopus and Science Direct. Manual search from grey literature; Google Scholar, and various natural product databases. Findings that were achieved to evaluate the pharmacological activity of Pinus gerardiana Wallich ex. D. Don. plant relation to distinct health issues reported to human was mentioned till 2020 in this review. Results: Pinus gerardiana Wallich ex. D. Don. (Chilgoza) seed, bark and leaves constituents are used in various part of the world as potential ayurvedic medicine and nutraceuticals. Phytochemical studies on Pinus gerardiana exposes the presence of Linoleic acid, oleic acid, albumenoids, oil starch, Phytosterol,Polyphenols, xanthenes, carotenoids, tocopherols, gallocatechin, catechin, lutein, etc. Different vitamins, including vitamin E, thiamin (B1), beta carotene, riboflavin (B2), niacin (B3), vitamin k, pantothenic acid (B5), vitamin B6, folate (B9), and minerals including magnesium, calcium, manganese, phosphorous, potassium, iron, zinc has been reported. Quantification of the constituents in seed and other parts has been mentioned. The plant shows various biological activities such as antioxidant activity, antithrombotic and anti-platelet activity, antidiabetic activity, anti-inflammatory activity, antifungal activity, antibacterial activity on scientific evaluation. Other than the plant reports miscellaneous activities, ectomycorrhiza and fungal diversity, inhibition of sperm parameters, bio-sorbent activity, aflatoxin contamination, nutraceutical value of different parts present in it. A section with plant's demerits, organochlorine pesticidal residues has been reported. Beside this short shelf life of chilgoza and method for extension, dysgeusia effect of the plant, associated allergic reactions and its conservation status has been elaborated till date. Conclusion: Chilgoza nut is enriched with oil, containing linoleic acid and other chemical constituents having health promoting impact on blood pressure, as well as cholesterol. This plant has a very high nutritional value with a high number of proteins, moisture, carbohydrates, fat, roughage as well as mineral content, that is why edible in the rural belt of the Himalayas. the plant is regarded as endangered now in India due to its high demand and human exploitation. In the article, we have described its chemical constituents, pharmacological importance, pharmacognosy, miscellaneous activities, nutraceutical value, molecular study, conservation status along with demerits as cited earlier in different kinds of literature .